How do students apply the octet rule and how do they justify this application? - Keller David; Hermanns Jolanda (Chemistry Teacher International, 2023)
In this paper we describe an intervention study on the application of the octet rule. This study was conducted at a German University with students in their first- and second undergraduate year. As repeatedly observed by us before, the evaluation of the study confirmed that the students have difficulties with the application of the octet rule in general, but above all for charged molecules. After an intervention, which consisted of a detailed checklist for the application of the octet rule and training opportunities, the students’ competences increased, especially for the tasks which included charged molecules. Students’ explanations were not as good as expected; the linguistic quality did not increase significantly from pre-to post-test. This is not surprising, because the training of argumentation skills was not part of the intervention. The intended goal, training the application of the octet rule, has been achieved.